Novel “The Violence within the Time” From the sociological perspective - Sifuentes León, Eudosio (2010)
The story «The Violence within the Time» is analyzed as a social and cultural universe where the history, the biography, daily life and the social structure acquire a complex and fascinating dynamic which is tackled from the interaction and the social networks. The analysis follows the sequence of the stories´ world delimited by scenarios, facts, organizations, real and fictitious characters from an imaginary town in Congara in Piura to the cities in Lima, La Habana, Paris and Barcelona, showing their different worlds and changing life styles, generational, ethnic, racial, status, social class, debates, reflections, wars, costumes, dreams and love encounters and discrepancies having as a main stream the adventure of Martin Villar in his attempt to understand his cultural identity and his tangled family background.